Bioenergy engineering : fundamentals, methods, modelling, and applications - Shadangi, Krushna Prasad (Woodhead Publishing, 2023)
Bioenergy Engineering: Fundamentals, Methods, Modelling, and Applications presents the fundamental principles, recent developments, innovative state-of the-art technologies, challenges, solutions and future perspectives on the production of biofuels and bioenergy. Balancing the scientific and engineering aspects of biofuels production, the book guides readers through the chemical kinetics, modeling, thermodynamics, unit operations and technological advancements in fuel processing from conventional and alternative resources. Each chapter of the book starts with the fundamentals and goes on to assess the latest technologies for the production of renewable fuels on topics.